Dynamic Performance of the Standalone Wind Power Driven Heat Pump. (December 2016) - Li, Hailong; Campana, Pietro Elia; Berretta, Sara; Tan, Yuting; Yan, Jinyue
Abstract: Reducing energy consumption and increasing use of renewable energyin the building sector arecrucial to the mitigation of climate change. Wind power driven heat pumps have been considered as a sustainable measure to supply heat for detached houses, especially those that even don't have access to the grid. This work is to investigate the dynamic performance of a heat pump system directly driven by a wind turbine. The heat demand of a detached single family house was simulated in details. According to the simulations, the wind turbine is not able to provide the electricity demanded bythe heat pump all the time due to the intermittent characteristic of wind power. To solve it, an electric energy storage system was included. Obviously, increasingthe size of battery can always reduce the probability of load loss. However, different from the energy storage system, increasing the capacity of wind turbines is not necessary to reducethe probability of load loss instead, due to the different start-up speedsfor different capacities of wind turbines. In order to maximize the system benefit, it is of great importance to optimize the capacity of the wind turbine and the size of the energy storage system simultaneously based on dynamic simulations.